Phototherapy as a Rational Antioxidant Treatment Modality in COVID-19 Management; New Concept and Strategic Approach: Critical Review - Reem Hanna; Snehal Dalvi; Tudor Sălăgean; Ioana Roxana Bordea; Stefano Benedicenti (MDPI AG, 2020)
The COVID-19 pandemic has taken the entire globe by storm. The pathogenesis of this virus has shown a cytokine storm release, which contributes to critical or severe multi-organ failure. Currently the ultimate treatment is palliative; however, many modalities have been introduced with effective or minimal outcomes. Meanwhile, enormous efforts are ongoing to produce safe vaccines and therapies. Phototherapy has a wide range of clinical applications against various maladies. This necessitates the exploration of the role of phototherapy, if any, for COVID-19. This critical review was conducted to understand COVID-19 disease and highlights the prevailing facts that link phototherapy utilisation as a potential treatment modality for SARS-CoV-2 viral infection. The results demonstrated phototherapy's efficacy in regulating cytokines and inflammatory mediators, increasing angiogenesis and enhancing healing in chronic pulmonary inflammatory diseases. In conclusion, this review answered the following research question. Which molecular and cellular mechanisms of action of phototherapy have demonstrated great potential in enhancing the immune response and reducing host-viral interaction in COVID-19 patients? Therefore, phototherapy is a promising treatment modality, which needs to be validated further for COVID-19 by robust and rigorous randomised, double blind, placebo-controlled, clinical trials to evaluate its impartial outcomes and safety.